2019
DOI: 10.1029/2018gc008082
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Oxide Concentrations in Natural Waters on Early Earth

Abstract: A key challenge in origins‐of‐life studies is estimating the abundances of species relevant to the chemical pathways proposed to have contributed to the emergence of life on early Earth. Dissolved nitrogen oxide anions ( NOX−), in particular nitrate ( NO3−) and nitrite ( NO2−), have been invoked in diverse origins‐of‐life chemistry, from the oligomerization of RNA to the emergence of protometabolism. Recent work has calculated the supply of NOX− from the prebiotic atmosphere to the ocean and reported steady s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 146 publications
(267 reference statements)
1
82
0
1
Order By: Relevance
“…Nitrate played an important role in magnetite synthesis. The concentration of nitrate used in the experiments is much higher than probably in the prebiotic seas (< 1 µmol L −1 ) [53]. Ranjan et al also suggested that nitrate concentration could be higher than 1 µmol L −1 in prebiotic pounds [53] Previous studies showed that depending on the concentration of sulfide, the concentration of iron in the early oceans could reach a value around 100 µmol L −1 [54][55][56].…”
Section: Implications For Prebiotic Chemistrymentioning
confidence: 94%
“…Nitrate played an important role in magnetite synthesis. The concentration of nitrate used in the experiments is much higher than probably in the prebiotic seas (< 1 µmol L −1 ) [53]. Ranjan et al also suggested that nitrate concentration could be higher than 1 µmol L −1 in prebiotic pounds [53] Previous studies showed that depending on the concentration of sulfide, the concentration of iron in the early oceans could reach a value around 100 µmol L −1 [54][55][56].…”
Section: Implications For Prebiotic Chemistrymentioning
confidence: 94%
“…Most readers are probably familiar with this quote, but we reiterate it here because Darwin's intuition of a warm little pond makes perfect sense. In contrast to the dilution that inevitably would occur in a global salty ocean, potential organic reactants can accumulate and be concentrated sufficiently for reactions to occur in small bodies of fresh water on volcanic land masses emerging from the ocean (Pearce et al, 2017;Ranjan et al, 2019). Darwin also proposed that a ''protein compound'' must first form, ''ready to undergo still more complex changes.''…”
Section: Damer and Deamermentioning
confidence: 99%
“…Effective attenuation of x-rays, cosmic rays, and UV light below 200 nm coexists naturally with direct sunlight in these atmospheres. The planet surfaces will provide access to metals (and nonmetals), namely, Fe and P, as well as trace amounts of HCN, SO 2 , H 2 S, and NO • in sufficient concentrations for prebiotic chemistry (12,60,74).…”
Section: Uv Irradiationmentioning
confidence: 99%